APPLICATION OF THE GOAL PROGRAMMING METHOD AND SENSITIVITY ANALYSIS IN OPTIMIZING BREAD PRODUCTION PLANNING - Zuhri Zuhri; Sri Rafiqoh; Hery Saputra (Adisam Publisher, 2024)
Umama Bakery's bread production process is considered less than optimal because the production quantity for each flavor variant is unlimited, resulting in insufficient raw materials at certain times. In addition, the order production process requires a long total completion time (makespan), resulting in delays in production completion (mean tardines). The aim of this research is to optimize total completion time, average delay time, use of raw materials used and optimize production income. This research uses the Goal Programming model with the Branch and Bound method. The results of the analysis using the Goal Programming model with the Branch and Bound method obtained an optimal solution, namely excess total completion time (makespan) of 36 minutes, excess average delay time (mean tardines) of 6 minutes, excess raw materials in raw materials. material availability is all zero, and sales revenue shortfall is zero. The results of the sensitivity analysis show that bread production at the Umama Bakery factory will remain optimal if there are changes in the availability of production completion time, delays in production time, and the availability of raw materials during these changes. variables are still within tolerance limits.